2017
DOI: 10.1002/2017gl072953
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional magnetotelluric inversion using reflection seismic data as constraints and application in the COSC project

Abstract: We present a novel 2‐D magnetotelluric (MT) inversion scheme, in which the local weights of the regularizing smoothness constraints are based on the envelope attribute of a reflection seismic image. The weights resemble those of a previously published seismic modification of the minimum gradient support method. We measure the directional gradients of the seismic envelope to modify the horizontal and vertical smoothness constraints separately. Successful application of the inversion to MT field data of the Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…One remedy to this non-uniqueness problem is to introduce additional model constraints or model regularisation (Jackson 1979;Tikhonov et al 1995;Zhdanov 2002;Menke 2012). The model constraints can enforce the conductivity distribution to vary smoothly (Constable et al 1987;de Groot-Hedlin and Constable 1990;Kalscheuer et al 2010), they can include prior geological knowledge, restrict the conductivity distribution by rock sampling tests, or be based on structural constraints (Gallardo and Meju 2011;Yan et al 2017b) and petrophysical constraints (Moorkamp 2017; Haber and Holtzman Gazit 2013) using information offered by other geophysical data sets (such as seismic, gravity, magnetic and logging data). Using a properly designed model constraint, the inversion algorithm can converge to a model that is close to the true model.…”
Section: Methods Of Model Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One remedy to this non-uniqueness problem is to introduce additional model constraints or model regularisation (Jackson 1979;Tikhonov et al 1995;Zhdanov 2002;Menke 2012). The model constraints can enforce the conductivity distribution to vary smoothly (Constable et al 1987;de Groot-Hedlin and Constable 1990;Kalscheuer et al 2010), they can include prior geological knowledge, restrict the conductivity distribution by rock sampling tests, or be based on structural constraints (Gallardo and Meju 2011;Yan et al 2017b) and petrophysical constraints (Moorkamp 2017; Haber and Holtzman Gazit 2013) using information offered by other geophysical data sets (such as seismic, gravity, magnetic and logging data). Using a properly designed model constraint, the inversion algorithm can converge to a model that is close to the true model.…”
Section: Methods Of Model Analysismentioning
confidence: 99%
“…a regular model weighting matrix m for which an inverse exists) introduce non-unimodularity, whereas singular first-or second-order smoothness constraints give unimodular resolving kernels. As a consequence, we advocate construction of a preferred inversion model using smoothness constraints with local modifications to account for known structural contrasts (e.g., Yan et al 2017b), if applicable. Other types of regularisation may introduce unintended bias and, in the absence of compelling prior evidence, reference models should only be used for hypothesis testing.…”
Section: Effects Of Model Regularisation On Model Uncertainty and Resmentioning
confidence: 99%
“…Further improvements in models of mineral deposits can be obtained by including resistivity borehole logs as local prior information (e.g., Yan et al 2017a), by transferring structural boundaries observed in reflection seismic images or seismic velocity models to 2D or 3D inversion models of MT data (e.g., Le et al 2016b;Yan et al 2017b;Moorkamp 2017) or by performing joint inversions of MT, seismic and potential field data using petrophysical or structural coupling (e.g., Moorkamp et al 2011;Gallardo and Meju 2011;Haber and Gazit 2013;Takam Takougang et al 2015;Moorkamp 2017). Strictly speaking, well logs only represent the resistivity structure up to a few metres off the borehole and may be affected by borehole fluids and the invaded zone around the borehole.…”
Section: Resultsmentioning
confidence: 99%
“…Many algorithms have been suggested to solve equation (5) (Van Beusekom et al, 2011;Candansayar, 2008;Mehanee and Zhdanov, 2002;Singh et al, 2017;Siripunvaraporn and Egbert, 2007;Yan P et al, 2017). In this paper, the smoothness-constrained leastsquares inversion method is adopted for solving the regularized inversion problems (Negi et al, 2013;Lee et al, 2009).…”
Section: Regularized Inversion Methodsmentioning
confidence: 99%